KEMATANGAN SOSIAL ANAK USIA DINI BERKEBUTUHAN KHUSUS (Studi Kasus pada Anak Tunadaksa) - Dian Ratnaningtyas Afifah; Prima Suci Rohmadheny (IKIP PGRI MADIUN, 2014)
This study aims to explore in depth the social maturity of an early childhood with special need in Sidoharjo Village, District Jambon, Ponorogo. Early childhood development is a critical moment, because in that period laid the foundations of behavior and brain as the center of human activity has improved significantly. One aspect that is developing at an early age is a social maturity, which include independence, motor skills, communication and social skills. The focus of social maturity in this study is the independence or ability to self help. The approach used in this study is a qualitative case study method type single case. The data collected in the form of primary data that is the result of observation and interviews conducted by researchers and secondary data in the form of documentation. The data then analyzed using analysis techniques Miles and Hubberman models with the following process:data collection, data reduction, data display, and conclusion or verification. The results showed that social maturity subjects with initials (FS) which is more focused on the aspects of self help demonstrate the ability, self help tend to be lower when compared with children his age. Shown with almost all activities carried out with the help of the subject closest especially the mother, this is because the motor organs tend to be rigid so it can not be used.